2015
DOI: 10.1149/2.0341603jes
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Analysis with Transmission Line Model for Reaction Distribution in a Pouch Type Lithium-Ion Battery by Using Micro Reference Electrode

Abstract: Electrochemical impedance spectroscopy (EIS) using an equivalent circuit is a powerful tool in the diagnosis of lithium-ion batteries (LIBs). However, LIBs have been increasingly used in applications requiring power higher than that used for conventional LIBs for portable electric devices. Considering this demand for LIBs, the ionic resistances in the electrodes, which raise a reaction distribution under high-power operation, are important. This consequently means EIS analysis should include ionic resistances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…18,21 In order to study electrode ageing mechanisms, Transmission Line Models (TLMs; a subset of ECMs) have previously been used to model the impedance response of porous electrodes infiltrated by a liquid electrolyte. 15,20,22,23 One important ability of these TLMs is the calculation of ionic resistance in the infiltrated pores R ion,L . The electronic resistance R el through the composite electrode is usually considered negligible compared to the ionic resistance.…”
mentioning
confidence: 99%
“…18,21 In order to study electrode ageing mechanisms, Transmission Line Models (TLMs; a subset of ECMs) have previously been used to model the impedance response of porous electrodes infiltrated by a liquid electrolyte. 15,20,22,23 One important ability of these TLMs is the calculation of ionic resistance in the infiltrated pores R ion,L . The electronic resistance R el through the composite electrode is usually considered negligible compared to the ionic resistance.…”
mentioning
confidence: 99%
“…At all the spectra, semicircles or collapsed semicircles are observed in the high frequency region of >100 Hz, indicating charge transfer through the surface film formed on the anode and cathode. 39,40 The resistance derived from these films increased with increasing cycle numbers. In the low frequency region, which is considered to be related to the solid state diffusion of lithium ion in the electrode bulk, 41 a linear line at 100th cycle changes into a part of collapsed semicircle at 400th cycle, indicating that the lithium ion diffusion is gradually inhibited with increasing cycle numbers.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, EIS is the method of choice to study the electrochemical properties of various battery electrodes as a function of cycling or state of charge [54]. Positive electrode active materials including V6O13 [14,55], LiMn2O4 [56,57] [72,73], LiNi0.5Mn1.5O4 [74], LiNi0.5Mn0.3Co0.2O2 [36,75], and LiNi0.6Mn0.6Co0.2O2 [76], as well as negative electrode active materials, such as carbons [35,60,68,[77][78][79][80], graphite [16,31,[36][37][38]57,[62][63][64][65][66][67][68][69][70][71][72][73][74][75]81,82], Sn-containing composites [82,83], LiTi2(PO4)3 [15], Li4Ti5O12 [61], and Si-containing composites [34,84,85] have...…”
Section: Electrochemical Impedance-based Techniquesmentioning
confidence: 99%
“…It has also been reported that overcharge conditions produce a high impedance at the positive electrode, while over discharge of the battery results in a higher impedance at the negative electrode [72]. Interestingly, when metallic Li is used as the negative electrode instead of a In general, three-electrode measurements have shown that the main contribution to the impedance of a LIB cell originates from the positive electrode [37,63,71,73,81]. The negative electrode, which generally comprises a graphitic active material, commonly exhibits a stable impedance contribution independent of the state of charge of the battery [63,71,73].…”
Section: Electrochemical Impedance-based Techniquesmentioning
confidence: 99%